Oral Administration of Achyranthis radix Extract Prevents TMA-induced Allergic Contact Dermatitis by Regulating Th2 Cytokine and Chemokine Production in Vivo - Sung Keun Jung; Dae Woon Choi; Da-Ae Kwon; Min Jung Kim; Ki Seung Seong; Dong-Hwa Shon (Molecules, 2015)
Allergic contact dermatitis (ACD) remains a major skin disease in many countries, necessitating the discovery of novel and effective anti-ACD agents. In this study, we investigated the preventive effects of Achyranthis radix extract (AcRE) on trimellitic anhydride (TMA)-induced dermatitis and the potential mechanism of action involved. Oral administration of AcRE and prednisolone (PS) significantly suppressed TMA-induced increases in ear and epidermal thickness, and IgE expression. In addition, abnormal expression of IL-1β and TNF-α protein and mRNA was also significantly attenuated by oral administration of AcRE. Treatment with AcRE also significantly suppressed TMA-induced IL-4 and IL-13 cytokines and mRNA expression in vivo. Moreover, AcRE strongly suppressed TMA-induced IL-4 and IL-5 production in draining lymph nodes, as well as OVA-induced IL-4 and IL-5 expression in primary cultured splenocytes. Interestingly, AcRE suppressed IL-4-induced STAT6 phosphorylation in both primary cultured splenocytes and HaCaT cells, and TMA-induced GATA3 mRNA expression ex vivo. AcRE also suppressed TMA-mediated CCL11 and IL-4-induced CCL26 mRNA expression and infiltration of CCR3 positive cells. The major compounds from AcRE were identified as gentisic acid (0.64 ± 0.2 μg/g dry weight of AcRE), protocatechuic acid (2.69 ± 0.1 μg/g dry weight of AcRE), 4-hydroxybenzoic acid (5.59 ± 0.3 μg/g dry weight of AcRE), caffeic acid (4.21 ± 0.1 μg/g dry weight of AcRE), and ferulic acid (14.78 ± 0.4 ± 0.3 μg/g dry weight of AcRE). Taken together, these results suggest that AcRE has potential for development as an agent to prevent and treat allergic contact dermatitis.